2022
DOI: 10.1186/s43055-022-00866-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of 18F-FDG PET/CT in evaluation of recently diagnosed breast cancer patients

Abstract: Background Breast cancer is the most frequent malignant disease in women and usually affects people of all ages, races, socioeconomic classes, and geographic locations. Once breast cancer is diagnosed, tumor staging should be assessed precisely before treatment and prognosis could be determined. The purpose of this study was to determine the diagnostic usefulness of PET/CT in the initial assessment of patients with newly diagnosed breast cancer who were referred for tumor staging, pre-therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Our results are also in line with a study of Gajjala et al [19] that examined 61 locally advanced breast cancer patients and declared that 18 F-FDG PET/CT staging had a higher accuracy than the conventional imaging staging. In the study of kamal et al [20], 50 women with newly diagnosed breast cancer showed higher diagnostic performance of 18 F-FDG PET/CT with % 100 sensitivity in comparison to 96 % sensitivity of contrast-enhanced CT. 18 Additionally, according to the NCCN guidelines, performing PET/CT examination may be more effective in detecting suspected nodal and distant metastatic involvement in locally advanced breast cancer stage III, but not advised for stage I, II, or operable III (T3 N1) breast cancer because of the high probability of false-negative results of the tiny lesions. The main limitation of this study was that it was performed at a single center as well as the relatively small sample size.…”
Section: Resultsmentioning
confidence: 94%
“…Our results are also in line with a study of Gajjala et al [19] that examined 61 locally advanced breast cancer patients and declared that 18 F-FDG PET/CT staging had a higher accuracy than the conventional imaging staging. In the study of kamal et al [20], 50 women with newly diagnosed breast cancer showed higher diagnostic performance of 18 F-FDG PET/CT with % 100 sensitivity in comparison to 96 % sensitivity of contrast-enhanced CT. 18 Additionally, according to the NCCN guidelines, performing PET/CT examination may be more effective in detecting suspected nodal and distant metastatic involvement in locally advanced breast cancer stage III, but not advised for stage I, II, or operable III (T3 N1) breast cancer because of the high probability of false-negative results of the tiny lesions. The main limitation of this study was that it was performed at a single center as well as the relatively small sample size.…”
Section: Resultsmentioning
confidence: 94%
“…18F-FDG PET-CT is currently regarded as an indispensable part of the evaluation of oncological patients due to its capacity to better characterise malignancy and added usefulness in correctly staging patients whose malignancy is later confirmed [ 1 ]. In oncology, tissue sampling is essential for making correct diagnostic and therapy decisions.…”
Section: Introductionmentioning
confidence: 99%